The role of digital and social media within mass media anti-smoking campaigns - Andy Lloyd; James Mckendrick; Ailsa Rutter (Tobacco Induced Diseases, 2018)
Background and challenges to implementation The evidence for mass media to raise awareness about the harm of smoking and benefits of quitting remains strong. However, pressures on budgets means TV is not always seen as an affordable option, while the emergence of digital media presents an attractive option to funders as a way of saving costs while maintaining responses. Digital and social media has provided us with learnings about the role of “push” (broadcast) and “pull” (direct responses) within campaigns and the balance of positive and negative messages.